A Case of Almost Painless Herpes Zoster Presenting with Symptoms of Cystitis, Penile Numbness, and Acute Vestibular Failure - Hussain Al-Sardar (Case Reports in Dermatological Medicine)
Herpes zoster (shingles) is an acute, painful, vesicular, and cutaneous eruption caused by varicella zoster virus, the same virus which causes chicken pox. It is due to the reactivation of the virus which remains dormant in sensory ganglions following chicken pox. It is usually confined to a single dermatome but may involve 2-3 dermatomes. Typically, it is a unilateral lesion which can affect both cranial and peripheral nerves. It is usually a self-limiting disease; however, it may cause significant morbidity especially in the elderly. It is more common in older people and individuals with immunocompromised conditions. Antiviral drugs can shorten the duration and the severity of the illness and need to be started as soon as possible after the appearance of the rash. Gabapentin and tricyclic antidepressant are effective in postherpetic neuralgia. Vaccine can reduce the risk of infection and its associated pain. Typically, it occurs once in a lifetime, but some individuals may have more than one episode.